Teaching clinical reasoning among undergraduate medical students: A crossover randomized trial - mona mlika; chadli dziri; manel jallouli; sarra cheikhrouhou; faouzi el mezni (Journal of Medical Education Development, 2023)
Background & Objective: Many clinical reasoning teaching techniques have been reported in the literature. The authors focused on 2 teaching techniques of clinical reasoning, the technique Summarize, Narrow, Analyze, Probe the preceptor, Plan, Self-selected topic (SNAPPS) and the Clinical Reasoning Technique (CRT), and compared their efficiency to improve the clinical reasoning competencies of third-year undergraduate medical students. Materials & Methods: The authors performed a prospective randomized, controlled, non-blinded crossover trial including year-3 undergraduate medical students. Judgment criteria consisted of the scores attributed to a test assessing the cognitive competencies of the participants which was a structured summary performed by the students after each session. Besides, a satisfaction Likert-scale questionnaire was fulfilled by the students. Statistical analysis was performed using SPSS software (version 20.0). Results: Seventy-two students were included with a mean age of 21.03 (SD:2,30) years. The mean scores of the students allocated to the CRT arm reached 4.62 (SD:2.93)versus 4.99 (SD:2.93) for the SNAPPS arm. No significant statistical difference was observed between the mean scores according to the method used. The analysis of the satisfaction questionnaire revealed that 75% of the students preferred CRT because of the collaborative work performed. Conclusion: This study highlights the need for varying techniques to improve the critical reasoning skills of medical students. Besides, it pointed out students' preference for collaborative approaches illustrating socio-constructivist theories of learning.